The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.22219/kembara.v7i1.15432
|View full text |Cite
|
Sign up to set email alerts
|

Leksikon kegulmaan pada masyarakat Jawa di Perkebunan Fajar Agung, Kecamatan Pegajahan, Kabupaten Serdang Bedagai: Kajian ekolinguistik

Abstract: Masyarakat Jawa Fajar Agung merupakan pekerja perkebunan yang sangat akrab dengan leksikon-leksikon kegulmaan. Keakraban ini dapat terlihat dari penggunaan leksikon yang masih bertahan sampai saat ini. Hal ini merupakan salah satu cara dalam pencegahan punahnya istilah Jawa dalam bentuk leksikon kegulmaan. Penelitian ini bertujuan untuk mendeskripsikan tingkat pemahaman masyarakat Jawa terhadap leksikon kegulmaan di Perkebunan Fajar Agung, serta menjelaskan faktor yang memengaruhi tingkat pemahaman masyarakat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
0
0
1
Order By: Relevance
“…Kemudian, penelitian kedua membahas leksikon kegulmaan pada masyarakat jawa di perkebunan Fajar Agung. Menyatakan bahwa kata kelgumaan dipengaruhi oleh faktor yang berkaitan dengan linguistik yang berhubungan dengan tendensi lingkungan masyarakat Jawa yang ada diperkebunan Fajar Agung terhadap bahasa Jawa (Putra et al, 2021).…”
Section: Pendahuluanunclassified
“…Kemudian, penelitian kedua membahas leksikon kegulmaan pada masyarakat jawa di perkebunan Fajar Agung. Menyatakan bahwa kata kelgumaan dipengaruhi oleh faktor yang berkaitan dengan linguistik yang berhubungan dengan tendensi lingkungan masyarakat Jawa yang ada diperkebunan Fajar Agung terhadap bahasa Jawa (Putra et al, 2021).…”
Section: Pendahuluanunclassified
“…Another study of Mbete et al, (2015) revealed that Lio language has a lexicon that is linguistically categorized including nouns, adjectives, and verbs, as a cultural process of managing natural resources, both clay resources in the context of pottery, as well as in the field of knowledge about plants and animals, cultural animals, ikat weaving, and also the marine world. Moreover, as shown in Putra et al, (2021), the environmental destruction such as by the use of chemical pesticides threaten and even diminish environmental resources such as weeds. This situation affects the understanding of the community about the certain plants and leads to the survival issue of the resources.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, research on lexicon knowledge has been carried out by three researchers, namely Swarniti & Yuniari (2019), Putra et al (2021), andArafiq (2021). First, Research by Swarniti & Yuniari (2019) describes the existence of a rare tree lexicon in Denpasar.…”
Section: Introductionmentioning
confidence: 99%
“…Second, research by Putra et al (2021) who examined the lexicon of weeds in the Javanese ethnic community in the Fajar Agung Plantation, Pegajahan District, Serdang Begadai Regency. The research found 75 lexicons of weeds.…”
Section: Introductionmentioning
confidence: 99%